(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2019)
Autoimmune Haemolytic Anaemia (AIHA) results from increased red cell destruction due to red cell autoantibodies. Pregnancy associated AIHA is a very rare condition with unexplained entity, but can be dangerous for both fetus and mother. A case of multipara lady who developed haemolyticanamia during pregnancy, with a wide range of differential diagnosis. She was responded well to moderate dose of steroid with good feto-maternal outcome. Autoimmune haemolytic anaemia in pregnancy has rarely been reported in literature, which deserve its presentation. JCMCTA 2019 ; 30 (1) : 61-63